Social Educational Work with the Pedagogical University Students - Future Social Teachers - Y. A. Makovskaya (Russian State Vocational Pedagogical University, 2015)
The paper discusses a model of social teachers' training for the higher school, and analyzes its approbation in several Ukrainian higher schools. The author accentuates the general pedagogical and special trainingprinciples, applied in the teaching course, and denotes the main criteria of the future teaches' readiness for professional activity. The research conclusions demonstrate that the social teacher training for the Master of Education degree involves the following factors: developed social educational network, pedagogical content guidance, intensification of training processes, motivation for professional self-development, and pedagogicalidentification. The pedagogical content guidance and training process intensification imply the combination of psycho-pedagogical disciplines and other professional courses, elaboration of didactic materials, educationalforms and methods. The pedagogical professional identification and motivation development provides the integrity of the value oriented, operational, and reflective components. The development of pedagogical identification is regarded as a complex dynamic phenomenon similar to socialization processes with their consequent stages of trust, autonomy, initiative, achievement, identity, creativity, and integrity.